The Motion of an Azobenzene Light‐Controlled Switch: A Joint Theoretical and Experimental Approach. Issue 3 (21st February 2019) - Godde, Bérangère; Jouaiti, Abdelaziz; Mauro, Matteo; Marquardt, Roberto; Chaumont, Alain; Robert, Vincent
Abstract: To gain further insight into the internal motion of molecular objects, we have synthesized a molecular turnstileAzoT composed of a rotor based on flexible tetraethyleneglycol (TEG) chains grafted on aromatic moieties and a stator containing a photoswitchable azobenzene (Azo) fragment. The control of the reversible light‐induced E ‐AzoT ⇆ Z ‐AzoT isomerization is supported by both NMR spectroscopy and photophysical investigation, which show that the system exhibits a fatigueless isomerization switching process. Furthermore, 2D NMR spectroscopy points to the fact that the free internal motion is triggered by the E ‐AzoT ⇆ Z ‐AzoT isomerization. Using molecular dynamics simulations and DFT calculations we have investigated the nature of the internal motions. An internal rotation characterized by an energy barrier of 23 kJ/mol is found for the Z ‐AzoT isomer. In contrast, this barrier reaches 151 kJ/mol for the E ‐AzoT isomer, excluding any "classical" rotation at room temperature. This rotational movement could in principle occur via tunneling. A simple model calculation, however, excludes tunnelling to take place before 20 ms. Abstract : Move it, move it : A molecular turnstile, AzoT, composed of a rotor based on tetraethyleneglycol chains grafted on aromatic moieties and a stator containing a photoswitchable azobenzene fragment, was synthesised. NMR spectroscopy, photophysical studies, DFT calculations and molecular dynamics simulations were combined to study the internal motion of this molecular object.